2016
DOI: 10.1158/0008-5472.can-15-2932
|View full text |Cite
|
Sign up to set email alerts
|

miR-339-3p Is a Tumor Suppressor in Melanoma

Abstract: Determinants of invasion and metastasis in cancer remain of great interest to define. Here, we report the definition of miR-339-3p as a novel tumor suppressive microRNA that blocks melanoma cell invasion without affecting cell survival. miR-339-3p was identified by a comprehensive functional screen of a human miRNA mimetic library in a cell-based assay for invasion by the melanoma cell line A375. miR-339-3p was determined as a strong inhibitor of invasion differentially expressed in melanoma cells and healthy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 56 publications
2
61
1
1
Order By: Relevance
“…Aberrant expression of 5 miRNAs reported in this study (miRNA-3615, miRNA-342, miRNA-339, miRNA-182, and miRNA-4485) has been previously reported in relation to liver cirrhosis or HCC malignancy (29) as well as some other cancers such as lung adenocarcinoma (30) , melanoma (31) , colorectal cancer (32) (33) , gastric cancer (34) (35) , intrahepatic cholangiocarcinoma (36) , colon cancer (37) , and breast cancer (38) (39) . Recently Wojcicka et al employed next generation sequencing to investigate the expression of microRNA in tissue samples of HBV/HCV infected with liver cirrhosis and HCC.…”
Section: Discussionsupporting
confidence: 76%
“…Aberrant expression of 5 miRNAs reported in this study (miRNA-3615, miRNA-342, miRNA-339, miRNA-182, and miRNA-4485) has been previously reported in relation to liver cirrhosis or HCC malignancy (29) as well as some other cancers such as lung adenocarcinoma (30) , melanoma (31) , colorectal cancer (32) (33) , gastric cancer (34) (35) , intrahepatic cholangiocarcinoma (36) , colon cancer (37) , and breast cancer (38) (39) . Recently Wojcicka et al employed next generation sequencing to investigate the expression of microRNA in tissue samples of HBV/HCV infected with liver cirrhosis and HCC.…”
Section: Discussionsupporting
confidence: 76%
“…Many studies have shown that miRNAs can act either as tumor suppressors or oncogenes in various cancers through regulating target gene expression by binding 3′ untranslated regions and repressing transcription [6, 7]. Recently, lncRNAs have drawn attention as potential biological regulators involved in a wide range of cellular activities such as cell proliferation, apoptosis, migration, and invasion [8].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, miRNAs bind to messenger RNAs’ (mRNAs) 3′ untranslated region (3′ UTR), which result in the degradation or translated inhibition of mRNA [5]. Emerging evidence suggests that altered expressions of miRNAs are implicated in various tumor biological process, such as cell growth, proliferation, angiogenesis, migration, invasion and so forth, via regulating targeted genes, [68]. Kong et al demonstrated that miR-511, acting as tumor suppressor, could inhibited the abilities of proliferation of GC via targeting TRIM24 [9].…”
Section: Introductionmentioning
confidence: 99%